Stages of mechanical alloying during the synthesis of Sn-containing AB5-based intermetallics - Cerón Hurtado, N. M. (2010)
The mechanical alloying of a  La025Ce0.52Nd0.17Pr0.06-Ni-Sn mixture is studied by  X-ray diffraction, Scanning Electron Microscopy, Energy Dispersive Spectroscopy and Differential Scanning Calorimetry. Four stages were identified and characterized. Initial stage was observed at integrated milling times (tm) between 0 and 30 h. It is dominated by fracture of the larger particles of Sn and La0.25Ce0.52Nd0.17Pr0.06. Intermediate stage is observed between 30 and 50 h. Both fracture and cold welding controls the process. At this stage, compositional changes are detected due to solid-solid reaction. Ni and Sn particles are alloyed in the larger particles of La0.25Ce0.52Nd0.17Pr0.06. The Final stage is observed between 50 and 70 h. At this stage, the cycle of fracture and cold welding reaches steady state and no further changes in chemical composition are observed. At completion stage, only refinement is observed. A La0.25Ce0.52Nd0.17Pr0.06Ni4.7Sn0.3 intermetallic is obtained.  The compound is thermally stable up to 180 °C in Air.